Wear Behaviour of Eutectic Al-Si Alloy-Graphite Composites Fabricated by Combined Modified Two-Stage Stir Casting and Squeeze Casting Methods - P. Shanmughasundaram; R. Subramanian (Advances in Materials Science and Engineering)
Dry sliding wear behaviour of eutectic Al-Si alloy-graphite composites was investigated employing a pin-on-disc wear test rig. Results revealed that the wear and friction coefficients decreased linearly with increasing weight percentage of graphite particles. Wear resistance of the composite increased considerably with increasing sliding velocity at constant load. In contrast, the friction coefficient of Al-7.5 wt.% Gr composite increased when the sliding velocity was increased from 1 m/s to 2 m/s at 49 N. Worn-out surfaces of wear specimens after the test were examined by scanning electron microscopy to study the morphology of worn surfaces. EDS analysis was carried out to investigate the influence of mechanically mixed layer (MML) which comprises oxides and iron, and this acted as an effective tribolayer in enhancing the wear resistance at higher sliding velocity.